2018
DOI: 10.1101/442236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EZH2 influences mdDA neuronal differentiation, maintenance and survival

Abstract: Over the last decade several components have been identified to be differentially expressed in subsets of mesodiencephalic dopaminergic (mdDA) neurons. These differences in molecular profile have been implied to be involved in the selective degeneration of the SNc neurons in Parkinson's disease. The emergence and maintenance of individual subsets is dependent on different transcriptional programs already present during development. In addition to the influence of transcription factors, recent studies have led … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 70 publications
(127 reference statements)
0
8
2
Order By: Relevance
“…Opioid‐induced withdrawal is also associated with Ezh2 (enhancer of zester homolog 2) expression, which catalyzes H3K27me3 36 . Virally mediated overexpression of Ezh2 in the VTA represses genes for dopaminergic neuron survival and enhances morphine CPP 17 . We propose that prolonged exposure to oxycodone during adolescence increases the sensitivity to morphine later in adulthood via the suppression of adaptive gene expression.…”
Section: Discussionmentioning
confidence: 95%
“…Opioid‐induced withdrawal is also associated with Ezh2 (enhancer of zester homolog 2) expression, which catalyzes H3K27me3 36 . Virally mediated overexpression of Ezh2 in the VTA represses genes for dopaminergic neuron survival and enhances morphine CPP 17 . We propose that prolonged exposure to oxycodone during adolescence increases the sensitivity to morphine later in adulthood via the suppression of adaptive gene expression.…”
Section: Discussionmentioning
confidence: 95%
“…The highest expression of the Enhancer of zeste homolog 2 (EZH2) was found in NSCs, and the lowest expression was found in Mat organoids. EZH2 involved in stem cell renewal and maintenance is highly expressed in NSCs or progenitor cells of the cortex, but its expression decreases in differentiated neurons [39][40][41] . The expression of CDH1-a co-factor that is required for the regulation of cortical neurogenesis and survival 42 -was noticeably higher in the BEM group than in other groups.…”
Section: Matrisome Proteinsmentioning
confidence: 99%
“…And EZH2 is abundantly expressed in immature neurons, whereas its expression significantly reduced during the maturation of hippocampal neurons 93 . Moreover, EZH2 regulates the generation of mesodiencephalic dopaminergic (mdDA) neuron and maintains the proper subset identity and the survival of different mdDA neurons during neural development 94,95 . Knockdown of EZH2 effectively promotes mdDA neuronal differentiation during midbrain development 96 .…”
Section: The Role Of Prc2 In the Neurogenic Differentiation Of Stem Cellsmentioning
confidence: 99%
“…SOX19b knockdown decreases the EZH2 upsurge and H3K27me3 at the promoters of ASCL1a and NGN1 , thereby reducing NSCs proliferation and premature differentiation into neurons 100 . The selective EZH2 inhibitor EPZ005687 effectively reduces the H3K27me3 level in ventral midbrain‐derived NSCs (VM‐NSCs) and enhances its differentiation into mdDA neurons 95 . A study has reported a crosstalk between RNA m6A modification and histone modifications.…”
Section: The Role Of Prc2 In the Neurogenic Differentiation Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation